The Fry Chronicles : An Autobiography - Fry, Stephen (London Penguin Books, 2010)
Stephen Fry is not just a multi-award-winning comedian and actor, but also an author, director and presenter. He is one of the most influential cultural forces in the country. This title details some of the most turbulent and least well known years of his life.
Include Color Illustrations and Index
Keywords: Comedians -- Fry, Stephen, 1957- -- Television Personalities